Study of History of Al-Bukhari on the Differences and the Relevance of the Role of Islamic Education Institutions with Building Religious Plurality in Indonesia - Shobirin; Guntur Dwi Purwanto; Naqiyah; Mohamad Anton Athoillah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2021)
This article discusses the Hadith of Al-Bukhari's history about the differences and relevance of the role of Islamic educational institutions in building religious plurality in Indonesia. Indonesia is a country that has the motto bhinneka tunggal ika. The plurality of plurality is highly upheld and respected. This study was written using a qualitative method with a literature study as an approach. The type of data in this article is in the form of written narratives or documents contained in the publication of Hadith History of Al-Bukhari about the differences and related scientific works that have been published. The technique of collecting data is by tracing some related scientific publications. The analysis technique used is through the use of the takhrīj al-hadīth application which is followed by sharh al-hadīth, both al-turathi and al-mu'āsir. This article describes that the Hadith of Al-Bukhari's history regarding differences is seen as relevant to the role of Islamic educational institutions in building religious plurality in Indonesia.